PENGEMBANGAN MEDIA PEMBELAJARAN SMART BOX PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SEKOLAH DASAR - Afriyanti, Linda; Sri Enggar Kencana Dewi; Nor Kholidin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop Smart Box learning media on the subject of Pancasila education, the material of the meaning of the Pancasila principles in the elementary school community. This study uses the research and development method (Research and Development) with the ADDIE model consisting of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The trial subjects in this study were 22 fourth-grade students of Rejosari State Elementary School. The product development instrument developed was validated by material experts and media experts, and tested through two stages, namely small-scale trials and large-scale trials. The results of validation by the validator and product trials indicate that the Smart Box learning media on the material of the meaning of the Pancasila principles in the fourth-grade elementary school community is very feasible to use. This is obtained based on the percentage of validation results and product trials. The percentage results obtained respectively include material experts at 92%, media experts at 88%, student responses in small-scale trials at 90%, and in large-scale trials at 91.8% all results are included in the